MENINGKATKAN KEMAMPUAN LITERASI MEMBACA DAN LITERASI NUMERASI DENGAN GIAT LITERASI BERTEMA GASING - Meiva Marthaulina Lestari Siahaan; Zulkaidah Nur Ahzan; Fitriani Fitriani; Hesni Neno; Prudensius Manek; Yuliana Serli Danul; Rut Tae (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
This community service activity was held according to situation analysis and problems that occurred at SD Negeri Sasi Kefamenanu, East Nusa Tenggara. The main problem is the low ability of students to solve problem in reading numeracy literacy in AKM model. This service method is a service-learning method with the aim of improving students' reading literacy and numeracy literacy skills through GASING-themed literacy activities and increasing student motivation in learning through GASING-themed literacy activities. The results of the service activities show 1) students' initial ability to work on reading literacy and numeracy literacy questions as seen from the average percentage value of 54.10%, 2) providing GASING-themed reading literacy activities in the form of providing props in the form of letter trees, paragraph puzzles, providing GASING-themed numeracy literacy activities in the form of providing props in the form of number cards, pattern cards, and number paper, 3) students' ability to work on reading literacy and numeracy literacy questions after receiving GASING-themed literacy activities as seen from the average percentage value of 78. 70%, and 4) understanding the material conveyed through GASING-themed literacy activities, the service team provides a quick and easy way to solve literacy problems, students are also enthusiastic when the service team conveys the material, students also feel that the service team is guiding students in solving problems, students also feel excited in participating in activities, students feel interested in this activity and are willing to take part in similar activities. This indicates that this activity is beneficial for students and motivates students in learning to develop their literacy skills.